2020
DOI: 10.1016/j.annonc.2020.08.1698
|View full text |Cite
|
Sign up to set email alerts
|

1384P Prognostic factors for survival in patients with metastatic lung adenocarcinoma: Analysis of the SEER database

Abstract: characteristics and treatment. All cases were re-reviewed by an expert adjudicator. Accuracy and concordance between automated and manual methods are reported. Results: Automated extraction required significantly less time (<72 hours) than manual extraction (225 person-hours). Collection of demographic data (age, sex, diagnosis) was highly accurate and concordant with both methods, (96-100%). Accuracy and concordance were lower for unstructured data elements in EHR, such as ECOG performance status, date of sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…NAKAZAWA et al results suggested that existing liver and bone metastasis adversely affected the outcome of the disease (28). The presence of liver metastases was found to be the worst prognostic factor in patients with metastatic lung adenocarcinoma (29). As stated by RIIHIMÄKI et al, patients with liver and bone metastases had a decreased survival rate when they had metastatic lung cancer (30).…”
mentioning
confidence: 94%
“…NAKAZAWA et al results suggested that existing liver and bone metastasis adversely affected the outcome of the disease (28). The presence of liver metastases was found to be the worst prognostic factor in patients with metastatic lung adenocarcinoma (29). As stated by RIIHIMÄKI et al, patients with liver and bone metastases had a decreased survival rate when they had metastatic lung cancer (30).…”
mentioning
confidence: 94%